Small Scale Industry in Punjab - Monica Gupta, Dr. Monika Chopra (International Journal of Advanced Science and Technology, 2020)
Because of their job potential and contribution to total industrial production, smallscale industry occupies an significant position in Punjab. These also aid in resource usage and further contribute to the steady and staggered promotion of change. Government has taken a number of steps to support them, but with recent measures, small-scale industries are facing certain challenges. The main purpose of our research is to study the growth of the industry and to study the financial problems faced by Punjab’s small-scale industry.